The orchid recovery program at Illinois College – a successful blend of teaching, research and undergraduate student participation to benefit orchid conservation - Zettler, Lawrence (Universidad de Costa Rica, 2015)
A decade ago (1996), the Orchid Recovery Program was established at Illinois College – a private liberal arts college – to promote the conservation of rare orchids through propagation. The school’s rural loca- tion, small size (1,000+ undergraduate students), and heavy teaching load (= 12 hours/semester) posed seri- ous challenges to the establishment of this research program. Nevertheless, over the years several aspects of the College were identified, targeted, and integrated to successfully blend the student academic experience with orchid conservation.